Malaysia's tourism demand: A gravity model approach=Permintaan pelancongan di Malaysia: Pendekatan model graviti - Othman, Muhammad Hanif; Mohamad, Noorihsan; Mat Ghani, Gairuzazmi; Ariffin, Muhammad Irwan (Penerbit UMT, 2018)
The tourism sector in Malaysia has undergone substantial growths as a result of the efforts taken by the Ministry of Tourism in policy planning and implementation. It is the government’s long-term goal to make Malaysia as the most popular tourism destination. The growth of tourism sector in Malaysia can be measured by tourist arrivals and receipts. Since this industry is able to drive Malaysian economy forward, more studies should be done in determining factors that influence demand for tourism. Therefore, this study was conducted to identify the demand factors of tourist arrivals in Malaysia and estimate their relative importance. Through understanding the determinants of Malaysia’s tourism demand, the government can design strategies and policies to enhance Malaysia’s competitiveness as a tourist destination. This study employed the bilateral tourism flows gravity model. The model includes income level of origin country and exchange rate to control for international shocks. This study also includes supply actor which is number of hotel room availability. The data used includes 149 countries, including countries with small numbers of arrivals. The bilateral tourism flows gravity model was estimated using Least Squares Dummy Variable (LSDV). The finding shows that population of country origin, country that share common border with Malaysia, income level of origin country and OIC country are major factors that increase international tourist arrivals. Since this study principally analyses the issue from a macroeconomic perspective, it is suggested that future studies re-examine the issue by using micro level data such as survey data of inbound tourists. In doing so, such findings would be more precise and informative compared to studies reliant on macro data.